First records of Brachythemis impartita in peninsular Italy (Odonata: Libellulidae) - Condello, Emanuele Guido; Razzetti, Edoardo; Liuzzi, Cristiano; D’Agostino, Vittoria; Mastropasqua, Fabio (Fragmenta entomologica, 2017)
Two populations of Brachythemis impartita (Karsch, 1890) are here reported in peninsular Italy. The species was found for the first time in 2015 in Calabria in the area of the Angitola artificial lake (Maierato and Monterosso Calabro municipalities) not far from the Tyrrhenian coast. In 2016 the species was also observed in southern Apulia, along the banks of two artificial lagoons in the municipality of Ugento. Information are provided that confirm the habitat preferences of the species and a northward expansion.